Programming with Ruby - Anderson, Al.; Safari eBooks ([S.l.] : Virtual Training Co., 2003)
"Programming with Ruby introduces developers to the Ruby programming language. Ruby is a dynamic object-oriented language. Its heritage includes LISP, Smalltalk, Perl and other languages. The simple but powerful nature of Ruby makes it one of today's hottest languages to learn. VTC author Al Anderson guides you through the various constructs and library of the language providing you with the tools to create great software in Ruby." --Resource description page.
Title from resource description page (viewed July 28, 2011).
Presenter, Al Anderson.
Keywords: Ruby (Computer program language); Electronic books